How Does The Change in Ratio of Vascular Plants to Biocrusts After Revegetation on Desert Soil Affect The Soil Hydrology? - Wang, Xinyan; Ni, Yuanyue (Transactions on Environment, Energy and Earth Sciences, 2024)
Land desertification is one of the most serious challenges to the ecological environment in the world today, threatening the survival and development of mankind. China is one of the countries in the world with the most serious desertification problem, which causes land degradation, soil quality decline, reduced vegetation cover, sand and dust, and other catastrophic weather problems. Greening and afforestation is an effective measure to improve the local ecological environment of desertification, and different areas need to adopt different afforestation techniques, taking into account local climatic conditions and geological features. This study aims to rank the three basic types of sand-binding vegetation in terms of suitability to be cultivated in desert soil by evaluating their ability to absorb infiltrated water and find a suitable shrub/herb planting ratio to achieve sustainable development in the sand-controlled area.